Law, Politics, and Women: How were 'Aisyiyah's Cadres Involved in the Party? - Anom Wahyu Asmorojati; Fauzan Muhammadi (Fakultas Hukum Universitas Muhammadiyah Magelang, 2021)
The law has regulated the quota of women candidates for legislative members of at least 30%. This regulation has encouraged all political parties to seek female members. However, women who have the capacities and capabilities as members of the legislature are difficult to find. One possible reason is their low participation in political education in religious, social organizations, such as' Aisyiyah. This study aimed to analyze the cadre system of women's political education of 'Aisyiyah in the Partai Amanat Nasional (PAN). This research is a normative, empirical legal research with a qualitative phenomenological approach. The informants of this research were 'Aisyiyah cadres or activists who were PAN and the Legislature members. The results showed that the cadre system of women's political education in 'Aisyiyah was carried out naturally through a public leadership capacity-building program. The involvement of 'Aisyiyah women in PAN was not merely practical politics, but it was carried out for the sake of upholding the law in Indonesia. Therefore, they were not affiliated with one particular political party but spread to various political parties in Indonesia. Thus, the involvement of 'Aisyiyah women in PAN was not merely a political movement but a legal movement and da'wah of amar ma'ruf nahi munkar (enjoining the good and avoiding the bad).